A novel method for contrast-to-noise ratio (CNR) evaluation of digital mammography detectors. - Baldelli P; Phelan N; Egan G; Baldelli, P; Phelan, N; Egan, G (European Radiology, 2009)
The purpose of this study was to test a new, simple method of evaluating the contrast-to-noise ratio (CNR) over the entire image field of a digital detector and to compare different mammography systems. Images were taken under clinical exposure conditions for a range of simulated breast thicknesses using poly(methyl methacrylate) (PMMA). At each PMMA thickness, a second image which included an additional 0.2-mm Al sheet was also acquired. Image processing software was used to calculate the CNR in multiple regions of interest (ROI) covering the entire area of the detector in order to obtain a 'CNR image'. Five detector types were evaluated, two CsI-alphaSi (GE Healthcare) flat panel systems, one alphaSe (Hologic) flat panel system and a two generations of scanning photon counting digital detectors (Sectra). Flat panel detectors exhibit better CNR uniformity compared with the first-generation scanning photon counting detector in terms of mean pixel value variation. However, significant improvement in CNR uniformity was observed for the next-generation scanning detector. The method proposed produces a map of the CNR and a measurement of uniformity throughout the entire image field of the detector. The application of this method enables quality control measurement of individual detectors and a comparison of detectors using different technologies.